THE PECULIARITIES OF MANAGEMENT OF INNOVATIVE ACTIVITY - Мандражи, О. А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article pays the teacher’s attention to the insufficient research of personal qualities of principals of a general educational school (GES) with an innovative focus. It highlights the opinion that even a high level of innovative competence of the GES principal does not provide his successful managing innovative activity without posessing certain personal qualities. Based of the analysed literature, practical and personal experience, the stages of managing innovative activity and the main functions of the GES principal are distinguished, which makes possible to outline some of his most important personal qualities: decency, sensitivity, humanity, dominance, stress tolerance, striving for success, emotional balance, self-confidence, creativity, diplomacy, responsibility, exactingness, independence. As all these qualities can be brought up, developed and improved, school principals can and should possess them for successful innovative activity